2004
DOI: 10.1677/erc.1.00659
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–stromal interactions in the mouse and human mammary gland in vivo

Abstract: This review deals with the development and hormonal responses of mouse and human mammary glands. A major focus of the review is the role of mesenchymal-epithelial interactions in embryonic mammary development and the role of stromal-epithelial interactions in mammary gland biology. Finally, we present a new model for studying growth, differentiation and hormonal response in human breast epithelium grown in vivo in nude mouse hosts. This new model involves the construction of tissue recombinants composed of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
149
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(151 citation statements)
references
References 103 publications
0
149
0
2
Order By: Relevance
“…However, in young adult (PND 60) mice, the number of TEBs was influenced by maternal separation events. By early adulthood, TEBs have guided the expansion of the ductal epithelial network to the distal boundaries of the fat pad and have begun to mature into morphologically distinct terminal LAUs (28,29). Relative to TR mice, those mice that experienced maternal separation events (BMS and LMS) had fewer immature TEB structures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, in young adult (PND 60) mice, the number of TEBs was influenced by maternal separation events. By early adulthood, TEBs have guided the expansion of the ductal epithelial network to the distal boundaries of the fat pad and have begun to mature into morphologically distinct terminal LAUs (28,29). Relative to TR mice, those mice that experienced maternal separation events (BMS and LMS) had fewer immature TEB structures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recently developed model has, for the first time, enabled examination of these interactions with human breast elements. Parmar and Cunha 34 implanted mammary fibroblasts together with mammary epithelial cells as xenografts under the renal capsules of female nude mice. These studies demonstrated the ability of stromal elements to interact with epithelial cells to enhance stimulation of mammary cell proliferation with estrogens.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that regulate embryonic mammary gland development have been reviewed recently (Parmar & Cunha 2004, Hens & Wysolmerski 2005. In brief, the Wnt signaling pathway, fibroblast growth factor signaling pathway, the Msx1/2 homeobox transcription factors, and parathyroid hormone-related protein play major roles in embryonic development and initial ductal growth (van Genderen et al 1994, Satokata et al 2000, Foley et al 2001, Mailleux et al 2002.…”
Section: Hormonal Control Of Mammary Developmentmentioning
confidence: 99%